DETERMINAN KUALITAS AUDIT INSPEKTORAT UTAMA BPK RI: Time Budget Pressure sebagai Variabel Moderasi - Fahmi Givari Akbar (2020)
The Big Four audit firms and the mid-tier audit firms in UK for the 2018/2019 cycle show problems of poor audit practices, which are indicated as audit failures. It causes sanctions and fines that significantly increase from the previous year. Furthermore, audit quality problems are also experienced by government internal auditors in Indonesia. The purpose of this study is to examine and prove empirically the influence of competence, independence, and motivation on audit quality which is moderated by time budget pressure. The population of this study is the government internal auditors who have worked at the Principal Inspectorate of Indonesia's Supreme Audit Institution. The sample consisted of 57 respondents and selected by purposive sampling method. The data analysis using Structural Equation Modeling (SEM) with SmartPLS software version 3.0. The results of the study conclude that competence and motivation significantly affect audit quality. Independence does not significantly affect audit quality. Time budget pressure does not moderate the effect of competence, independence and motivation with audit quality.